Written assignments in distance learning and communication with learners as part of the role of the lecturer in the distant education (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2017)
In this paper the authors tried to underline the importance of distance learning as a means of distant education in the contemporary educational system. A literature review which explains why such a survey is very important in terms of this kind of modern learning was implemented. A short revision of some very important past surveys around the topic of distance learning was carried out, especially in terms of the research questions and the methodological approach that past researchers used in order to dig deeper into the topic. Finally, the results of such empirical researches were analyzed and some critical thoughts of the authors are presented.